Quantitative Determination and Cytotoxic Effect of Oleanolic Acid from Olea europaea Leaves Extract Cultivated in Iraq - S Jaafar , Noor; A. Alshammaa, Dhuha; Abdul-lalil, Thukaa zuhair; M. Ibrahem, Nabaa (Iraqi Journal of Pharmaceutical Sciences, 2022)
Since its first description as a cytotoxic agent, Olea europaea leaves extract gained significant popularity against human breast cancer, ethyl acetate extract of Olea europaea leaves obtained by acid hydrolysis method was evaluated in vitro as cytotoxic agent against new human breast cancer (AMJ13) cell line, using the MTT assay. One main pentacyclic triterpenoid; oleanolic acid, was isolated from leaves of Olea europaea by well-known two different methods, but not used for this compound before, the acidic hydrolysis method and basic acidic method. The presence of oleanolic acid was proved in both methods with qualitative and quantitative determination using high performance liquid chromatography (HPLC), which was active against breast cancer AMJ13 cell line with IC50 value of 0.8936 ?g/ml.